PENGARUH LAMA FERMENTASI DAN KONSENTRASI BERAS SANGRAI TERHADAP BEKASAM IKAN PATIN (Pangasius sp) SEBAGAI RANCANGAN BOOKLET PADA KONSEP BIOTEKNOLOGI KONVENSIONAL KELAS XII SMA - Nada Haini; Imam Mahadi; Darmawati Darmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine the effect of fermentation time and roasted rice concentration on the quality of Pangas catfish (Pangasius sp.) and produce a booklet design on the conventional biotechnology concept of class XII SMA. This type of research is a quantitative research. The research was conducted in 2 stages. The first stage, namely the experimental stage, is the stage of making Pangas catfish marks. The method used was an experiment with a completely randomized design (CRD) with a 3x3 factorial pattern with 3 replications of the concentration of roasted rice and fermentation time. The fermentation time was 7 days, 14 days, and 21 days and the roasted rice concentration was 40%, 50%, 60%. The research parameters were fat content, protein content and pH. Furthermore, the second stage, namely the design of the booklet, includes the analysis and design stages. The results showed that the duration of fermentation and the concentration of roasted rice affected the quality of Pangas catfish (Pangasius sp.) Marks with the parameters of fat content, protein content and pH where the best quality of catfish (Pangasisus sp) was found in the T3P3 treatment (21 days of fermentation. and roasted rice concentration of 60%) which has a fat content of 1.4661%, a protein content of 10, 7841%, a pH value of 3.3. Based on the potential analysis, the research results can be used as a Booklet Design for Conventional Biotechnology Material for class XII SMA.Key Words: Booklet, fermentation time, roasted rice, Pangasius sp